INTEGRATED FOOD SECURITY MANAGEMENT USING SIPEKAN (FOOD SECURITY MONITORING INFORMATION SYSTEM) - Sasana, Hadi; Purbaningrum, Catarina Wahyu Dyah; Rohmah, Siti; Afriyanti, Afriyanti; Rochmadi, Imsak; Suprapto, Agus; Bharata, Risma Wira; Negara, Julius Galih Prima (Jurnal REP (Riset Ekonomi Pembangunan), 2025)
The study aims to investigate an integrated food security management using the Food Security Monitoring Information System, called “SIPEKAN” (Sistem Informasi Pemantauan Ketahanan Pangan) in Gunungkidul Regency, Yogjakarta, Indonesia. This study is a research and development-type of research (Research and Development) with the development model presented by Plomp (2013). The target groups are the community, farmers, agricultural extension workers, the agricultural service, the trade service, and the local government of Gunungkidul Regency. This research is expected to provide an integrated food security management equipped by the Food Security Monitoring Information System, called "SIPEKAN", which can be one answers to ensure food security in Gunungkidul Regency. By using SIPEKAN, it is projected that the community/farmers will easily sell their agricultural products, agricultural field workers will easily input agricultural potential data in each assisted area, the agricultural office and trade office will easily monitor product availability in each area in Gunungkidul Regency, and the Gunungkidul Regency Government can also employ the monitoring results provided by information system as a basis for policy making.